Calcium and iron-rich maternal cereal drink with sesame seed (sesamum indicum) flour - Cancino, Venice C.
This study aimed to develop a calcium and iron-rich maternal cereal drink mix with sesame seed flour (SSF) as replacement to wheat flour (WF) and to evaluate the product in terms of phytic acid content, consumer acceptance, proximate composition, iron and calcium contents, and physico-chemical properties. Phytic acid content of SSF was significantly (p < 0.05) reduced by roasting. Four cereal drink mixes with varied SSF-WF content (0%SSF-100%WF, 10%SSF-90%WF, 25%SSF-75%WF and 40%SSF-60%WF) were subjected to consumer acceptance test in terms of over-all acceptability, appearance, aroma, flavour and consistency. Significant differences (p < 0.05) were found in terms of aroma, flavour and over-all acceptability. SSF-WF (10:90) was the most acceptable in terms of flavour and over-all acceptability. Proximate composition of the two samples was found to be significantly different (p < 0.05) except in moisture content. No significant differences were found between the calcium and iron contents of the samples. Color and total soluble solids of the samples were significantly different (p<0.05), but their water activity was not. The Recommended Energy and Nutrient Intakes, based on pregnant women aged 19-29 years, of SSF-WF (10:90) were: 4.9679% for protein, 6.2003% for energy, 5.6294% for calcium, and 3.6748% for iron. Replacement of WF with SSF caused an increase in the amounts of some nutrients. Absence of significant difference (p < 0.05) in some parameters could be due to the low SSF percentage used or ineffective phytic acid reduction treatment. Further studies are recommended to obtain better results.